2020
DOI: 10.1111/1440-1703.12133
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term observation of fish community in streams inside and outside road construction of Teshio River system, northern Hokkaido, Japan

Abstract: Nakagawa experimental forest of Hokkaido University is located in the middle Teshio River and some tributaries flow through the forest. The construction of Otoineppu bypass route started in 2007. This bypass route will pass through the forest. In order to evaluate the impacts of the road construction on stream ecosystem, a long-term monitoring of fish community and stream environmental characteristics have been conducted including before, during and after the road construction. The survey has been implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Fish abundance gradually increased in one of the branches of the Teshio River (Umatani et al, 2020). However, white‐tailed eagles usually take their prey in the mainstream and riverbed ponds of the Teshio River but not in branches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fish abundance gradually increased in one of the branches of the Teshio River (Umatani et al, 2020). However, white‐tailed eagles usually take their prey in the mainstream and riverbed ponds of the Teshio River but not in branches.…”
Section: Discussionmentioning
confidence: 99%
“…These species prefer slow‐flowing basins and still waters and constituted the main prey of white‐tailed eagles (see Section 3). Umatani et al (2020) reported a gradual increase in fish abundance from 1999 to 2017 in one of the branches of the Teshio River.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation